Degenerative action on mice and rat testes of polyspermine and its complexes with RNase A - Matoušek, Josef; Tománek, Milan; Vottariello, Francesca; Morbio, Manuela; Gotte, Giovanni; Libonati, Massimo (Journal of Applied Biomedicine, 2007)
A significant aspermatogenic activity, ascertained by microscopic studies of seminiferous tubules and interstitial tissue, and by the observation of the entrance of immunity and fibrocytic cells in mice injected with polyspermine (PS) or polyspermine conjugated to monomeric or dimeric RNase A (PS-RNase A or PS-dimeric RNase A, respectively), was found either in mice injected or in non-injected testes. Polyspermine and its complexes with RNase A destroyed all spermatogenic and intertestitial tissue, including Leydic cells, as well as their ability to secrete testosterone. The total loss of spermatogenic activity in injected testes is irreversible because spermatogonia cells also were destroyed. The injection of PS into both mice testes determined the total degeneration of testicle tissue in 50% of injected testes. The second half of testes was also partly degenerated, and if they were re-injected, almost all testes were fully destroyed. PS-dimeric RNase A injected once into both testicles produced a stronger degeneration and also the interruption of testosterone secretion in comparison with the effects due to injection of mice with PS or PS-RNase A. In all mice treated with these substances, as well as in rats in which PS was injected twice into their testes, we detected polymorfonucleates, monocytes, plasma cells, lymphocytes.and fibrocytic cells. Antibodies against PS, PS-RNase A or PS-dimeric RNase A did not influence the aspermatogenic activity. Animals in which a repeated intra-peritoneal injection was carried out did not lose body mass and remained in good condition, with the exception of mice injected with spermine.
Keywords: Cells; Antispermatogenic Agents; Spermine; Spermatogenesis; testis; ribonukleasy; buňky; spermin; financování organizované; Ribonucleases; Financing, Organized; potkani Wistar; antispermatogenní látky; Mice, Inbred ICR; Rats, Wistar; Testis; Data Interpretation, Statistical; spermatogeneze; myši inbrední ICR; interpretace statistických dat